(untitled) (Eureka Journal of Education & Learning Technologies, 2026)
The article discusses the history of foreign language teaching methodology and its stages of development. It explores how language teaching methods have evolved from traditional grammar-based approaches to modern communicative and task-based techniques. The research highlights the main principles, goals, and changes that occurred throughout history in response to social and educational needs. The findings emphasize that each stage in the development of methodology has contributed to improving the quality of teaching and learning foreign languages.